Pell-Padovan generalized quaternions - Isbilir, Zehra; Gurses, Nurten (BULGARIAN ACAD SCIENCE, 2021)
The aim of this article is to introduce Pell-Padovan generalized quaternions. It also derives new properties associated with these and takes into account negative indices. Additionally, it presents generating function, Binet-like formula, Simson formula, matrix representations, and several summation properties.
Keywords: Pell-Padovan numbers; Generalized quaternions; Generating function; Binet-like formula; Simson formula; PERRIN; SEQUENCES; Mathematics